Mechanical Behavior Investigation of UHMWPE Composites for Pile Cushion Applications - Tulatorn, Viewvana; Ouajai, Sirisart; Yeetsorn, Rungsima; Chanunpanich, Noppavan (Applied Science and Engineering Progress, 2015)
Presently, there is no specific guiding principle on the utilization of polymeric composites as a pile cushion pad. There is a prerequisite consequently to understand their mechanical behavior during a pile driving process. Hence, this article is concerned with the observations of mechanical behavior under cyclic loading application, compressive strength, coefficient of restitution, and permanent deformation of ultrahigh molecular weight polyethylene (UHMWPE) and activated carbon (AC) composites. UHMWPE/AC composites containing 1, 3, 5, 10 and 20 wt% of AC concentrations were prepared for accomplishing the aim. Prior to those characterizations, the composites were compression molded under 160ºC for various operating times (5 to 40 minutes). As a comparison to UHMWPE, applying AC into UHMWPE matrix significantly reduced the cycle time of the compression molding. Compressive strength at 80% deformation, tangent modulus and coefficient of restitution of UHMWPE were inferior to those properties of UHMWPE/AC composites. In terms of the coefficient of restitution, the coefficient values of composites were obviously higher than UHMWPE’s values. Moreover, the coefficient of restitution at 8,000 N/min of all samples was greater than a represented coefficient from the test at 2,000 N/min. UHMWPE/AC composites with 10 wt% of AC loading provided the best mechanically reversible performance. Experimental results also indicated that the mechanical property enhancement associated with an increase in UHMWPE’s molecular weight, while the creep strain of UHMWPE was affected by the applied amount of AC. Permanent deformation data illustrated that the increasing cycles of compression urged the deterioration as same as the results measured via cyclic compression testing. In overview, UHMWPE/AC composites showed a promise for future opportunities as a viable option in replacing a traditional material for manufacturing a pile cushion pad.